Роль углубленного анализа комплементарности торговли для оценки эффективности международного бизнеса в условиях имплементации Соглашения об ассоциации Украины и ЕС - Архиереев, Сергей Игоревич (НТУ "ХПИ", 2015)
Для углубленного анализа комплементарности торговли ведены новые факторные индексы – комплементарности экспорта анализируемой страны и комплементарности импорта партнера, способствующие оценке реализации потенциала комплементарности торговли. Проведены их расчеты для Украины, с одной стороны, ЕС и Германии – с другой, в условиях начала имплементации Соглашения об ассоциации Украины и ЕС. Показано, что начальный этап имплементации практически не повлиял на реализацию потенциала торговой комплементарности и эффективность международного бизнеса в Украине.

For the profound analysis of a trade complementarity, the new factor indexes (export complementarity of the analyzed countries and the import complementarity of the partner), promoting an assessment of realization of potential of a trade complementarity, are introduced. Their calculations for Ukraine from one side, the EU, and Germany from other side in the conditions of the beginning of implementation of the EU-Ukraine Association Agreement are carried out. It is shown that the initial stage of implementation practically did not influence on realization of potential of a trade complementarity and the international business efficiency in Ukraine.
A role of the profound analysis of trade complementarity for assessment of efficiency of the international business in conditions of implementation of the EU-Ukraine Association Agreement
Keywords: экспорт; импорт; Германия; export; import